Development and implementation of environmental strategies for steel industry. (14th January 2008) - Singh, R. Kumar; Murty, H. Ramalinga; Gupta, S. Kumar; Dikshit, A. Kumar
Environmental issues in steel industry are so numerous, complex, and interconnected that an ad hoc approach to problem solving is no longer considered effective. The growing pressure from all stakeholders forces steel companies to adopt environmental responsibility in all activities. There has a paradigm shift in the attitude of the steel corporate as it switches over from 'Passive environmental strategies 'to Proactive environmental strategies'. In this paper, Importance?Performance Analysis (IPA) offers a simple, yet useful method for simultaneously considering both the importance and performance dimensions when evaluating or defining environmental strategy. This study uses IPA to identify environmental strategies as distinctive sets of environmental management activities and evaluate environmental strategies. The major findings of the study indicate that industry needs to develop robust methodology to monitor Environment Performance Indicators (EPIs) and perform benchmarking with competitors, conduct environmental risk assessment, improve their hazardous waste management practices, and make environmental investments on regular intervals.